2020
DOI: 10.5334/gh.384
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes and Factors Associated with Mortality in Patients with Moderate to Severe Pulmonary Hypertension in Kenya

Abstract: Background: Pulmonary hypertension is poorly studied in Africa. The long-term survival rates and prognostic factors associated with mortality in patients with moderate to severe pulmonary hypertension (PH) in Africa are not well described. Objectives:To determine the causes of moderate to severe PH in patients seen in contemporary hospital settings, determine the patients' one-year survival and the factors associated with mortality following standard care. Methods: A retrospective review of patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In contrast, this rate was 5.7% in the study conducted by Nugunga et al . in Kenya [ 7 ] and was reported as 4.2% in the study conducted by Duffels et al . in Europe [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, this rate was 5.7% in the study conducted by Nugunga et al . in Kenya [ 7 ] and was reported as 4.2% in the study conducted by Duffels et al . in Europe [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the variability of etiological factors, the prevalence of PH in African countries is higher than in developed countries [ 4 , 5 ]. Studies on mortality in a small number of countries on the continent have shown that PH is the leading cause of death [ 6 , 7 ]. Somalia, where our study was conducted, has a special place among African countries; in this country, there is no social security system and social state policy due to the ongoing civil war [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, a total of fifteen studies were selected which, all in all, reported on a total of 127,215 participants and 73,999 incident cases published from 2005 to 2020. Most of relevant studies were conducted in US ( n = 8) ( 7 , 12 , 18 , 19 , 30 , 32 , 35 , 37 ), while others were run in China ( n = 2) ( 20 , 31 ), Kenia ( n = 1) ( 34 ), France ( n = 1) ( 38 ), Italy ( n = 1) ( 33 ), Israel ( n = 1) ( 17 ), Australia and New Zealand ( n = 1) ( 36 ). All studies focused on risk estimates for males and females.…”
Section: Resultsmentioning
confidence: 99%
“…In most of these publications, important cofounders such as age ( n = 7), smoking ( n = 2), and mediators including diabetes ( n = 6), hypertension ( n = 3) were adjusted in the analysis. Among the selected essays, six of them enjoy a rather high methodological quality (score ≥7) ( 7 , 18 , 20 , 34 , 37 , 38 ), while the other nine have a low quality (<7) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The situation may be further complicated by lack of awareness of CTEPH among physicians and patients, particularly where resources for healthcare education are devoted to more prevalent conditions [ 51 ]. The proportion of patients with PH who have CTEPH has been reported as 16% in Egypt [ 52 ], 5% in Kenya [ 53 ], and 2% in the Pan-African Pulmonary Hypertension Cohort (PAPUCO) Registry [ 54 ]. These observations suggest that the diagnosis and management of CTEPH may be especially challenging in the African continent.…”
Section: Discussionmentioning
confidence: 99%